Cloud Computing: a tool for effective records and information management system in Nigerian academic libraries - Okuonghae, Nosakhare; Bakare-Fatungase, Oluwabunmi Dorcas (Folia Toruniensia, 2023)
Academic libraries, as part of their traditional responsibility, engage in the collection and generation of data and records with a various degree of sensitivity and usefulness. This study examined the importance of library record and advocates for the implementation of cloud computing technology as a viable alternative to other mode of record storage. Cloud computing as a record management tool will help preserve the myriad of records generated from the daily activities of libraries. The paper also identified the danger of paper or electronic method of information storage. It argued that information stored in this format is susceptible to loss by theft, fire or computer viruses, hard drive collapse as well as the destruction of local library internet server due to poor maintenance culture on the part of the personnel. Apart from the data backup function, remote accessibility of these record is another key consideration for cloud computing utility in library record management. In view of the vast potential, especially in the area of its elastic storage capability, it is highly recommended for all academic libraries in the country. However, it is observed that the cost of data and irregular power supply are some of the challenges facing its adoption in Nigeria, as along with the vulnerability to cyber-attacks which may lead to a partial or total loss of record. In these regards, it is further recommended that cloud computing, as a service platform, is adopted as a backup platform rather than a sole tool for record and data management in academic libraries.